ULAMA, AL WASHLIYAH AND KNOWLEDGE IN MODERN INDONESIA (1930-1980) - Ja'far, Ja'far (State Islamic University North Sumatra, 2022)
Abstract: This article examines the role of Al Washliyah ulamas in the development of knowledge in Indonesia. This study is a literature study, by applying Kuntowijoyo’s model, and utilizing historical and philosophical approach. Al-Attas' theory of the classification of knowledge will be used as a tool to analyze the topic of this study. The aim of this study is to find Al Washliyah scholars from 1930 to 1980 who played an important role in developing knowledge in Indonesia. This study argues that Al Washliyah ulamas have taken an important role in developing two types of knowledge, namely religious sciences; as well as the rational, intellectual and philosophical sciences, although their attention is more directed to the former. Their works cover the fields of the Qur’an, sunnah, shariah, theology, Islamic metaphysics (tasawuf), linguistics, comparative religion, philosophy, and history. They wrote using Latin script (Indonesian), Arabic script (Arabic) and Jawi script (Malay Arabic). The works of Al Washliyah ulamas have become a reference for their students and Muslims in East Sumatra and Aceh. Some of their works are still used as textbooks in a number of madrasas. This shows that their works are still in demand as proof that the influence of Al Washliyah scholars left an important mark.Keywords: ulama, Al Washliyah, classification of knowledge, religious sciences, rational sciences